PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL DAN KECERDASAN SPRITUAL PADA PERILAKU ETIS DENGAN PENGALAMAN SEBAGAI VARIABEL PEMODERASI - dewi, tiara kusuma; Wirakusuma, Made Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.09.TAHUN 2018DO - 10.24843/EEB.2018.v07.i09.p01, 2018)
This study aimed to examine the effects of intellectual intelligence, emotional intelligence and spiritual intelligence on ethical behavior with experience as a moderating variable. The data used in this study is the primary data obtained through questionnaires with auditors as respondents and measured using a 5 points Likert Scale. The analysis technique used is Moderate Regression Analysis (MRA) This Study finds that intellectual intelligence,  emotional and spiritual intelligence prove have a positive effect on the ethical behavior. In addition, this study found that the variable of experience had strengthen the influence of intellectual intelligence, emotional intelligence spiritual intelligence on ethical behavior.